Tinjauan Pelaksanaan Prosedur Keamanan dan Kerahasiaan Rekam Medis Pasien di RSUD Tebet - Annisa Ariyani (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2022)
Maintaining the confidentiality of the patient's medical record, required storage of medical records that meet the requirements in maintaining security and confidentiality. Medical record storage room can be said to be good if the room guarantees security and avoids the threat of loss, negligence, disaster and everything that can endanger medical records. The purpose of this study was to find out information about the security and confidentiality of medical records at RSUD Tebet. The research method used is descriptive qualitative approach by obtaining research information based on interviews and observations. The results of this study can be seen in the implementation of the security and confidentiality of medical records, there are provisions that have not been implemented, so that the security and confidentiality of medical records at RSUD Tebet is not maximized. The inhibiting factors for the smooth implementation of security procedures and the confidentiality of medical records cannot be separated from the facilities and infrastructure, such as the layout of the medical record storage room that is easily accessible by unauthorized parties, even though there is a finger print machine, there are still other medical record officers who enter to the medical record room. There are patients/patient families who come to the medical record room to ask for the patient's medical record data. Suggestions should be to emphasize and re-socialize the provisions that have been set in the existing Standard Operating Procedure policies to carry out activities in accordance with the provisions in force at the RSUD Tebet, for security, the medical record storage room is limited by access rights, such as the need to add a finger print access machine in the storage room to prevent unauthorized parties from entering the storage room.. Keywords: Security, Confidentiality, Medical records, Storage space